Soluble salt-driven matrix swelling of a block copolymer for rapid fabrication of a conductive elastomer toward highly stretchable electronics. (15th June 2016) - Hu, Mingjun; Zhang, Naibo; Guo, Qiuquan; Cai, Xiaobing; Zhou, Shaolin; Yang, Jun
Abstract: A simple soluble salt-driven matrix swelling method was developed for fast fabrication of a silver nanoparticle-based conductive elastomer. Taking advantage of the synergistic effects of silver trifluoroacetate and methanol, the swelling capability of an elastomeric block copolymer polystyrene- block -polyisoprene- block -polystyrene (SIS) was greatly enhanced. The interaction of silver ions and double bonds of the copolymer enables fast infiltration of soluble salt into the polymer network, resulting in a high-content loading of silver ions, which is a prerequisite for fabrication of a highly conductive polymer. In-situ reduction was performed under a swollen state to allow the reducer to effectively penetrate into the polymer matrix, thoroughly reducing the silver salt into silver nanoparticles. A three-layered conductive elastomer was obtained, with a high concentration of silver nanoparticles formed on both surfaces of SIS copolymer. Typically, the conductivity of the reduced SIS elastomer was measured to be > 2 × 10 5 S/m when ε = 0, and can maintain to be over one seventh of its initial value even at a 200% elongation. The conductive elastomer can withstand over 1000 stretch-release cycles under a strain of 100%. A radio-frequency antenna was prepared with the conductive elastomer, which gives the ability of dimension tuning, to realize high-quality frequency-selective radiation at a wide bandwidth of larger than 2.6 GHz. Graphical abstract: Highlights: Polystyrene- block -polyisoprene- block -polystyrene (SIS) rubber was found significantly swollen in high-concentration silver trifluoroacetate methanol solution, resulting in high silver salt loading and consequently high silver nanoparticles filling ratio in rubber matrix after in situ reduction, to generate highly conductive elastomer under large deformation, which show great promise in stretchable electronics.